Effects of Unconventional Water Agricultural Utilization on the Heavy Metals Accumulation in Typical Black Clay Soil around the Metallic Ore - Liang Pei; Chunhui Wang; Liying Sun (Toxics, 2022)
Unconventional water is an important water resource for agricultural utilization in the drought and water shortage of Northeast China. Additionally, exploration in making full use of it is an important way to alleviate water shortage in China. This paper analyzed the effects of unconventional water through field trials on the accumulation of heavy metals in both cucumbers and the typical black clay soil (expressed as black soil) around the Anshan metallic ore. By exploring the effects of unconventional water after secondary treatment on the accumulation characteristics of heavy metals in cucumbers and the heavy metal balance in the soil–crop system under different conditions, the study shows that there are no significant differences in the heavy metal content when the quantity of unconventional water for irrigation varies. Unconventional water for short-term irrigation does not cause pollution to either the soil environment or the crops. Nor will it cause the accumulation of heavy metals, and the index for the heavy metal content is far below the critical value of the trade standard and national standard, which indicates that the crops irrigated with unconventional water during their growth turn out to be free of pollutants. Unconventional water brings less heavy metals into the black soil than crops. The input and output quantities have only small effects on the heavy metal balance in the black soil. This paper provides a reference for the safety control and evaluation of unconventional agricultural utilization.